Urban–Suburban Relations and Quality of Life Along the Maribor–Graz Corridor: A Study of Four Settlements in Northeast Slovenia - Davidović, Danijel; Kumer, Peter (Quality of Life in a Changing World: Spatial, Social and Environmental Perspectives from Maribor and Beyond, 2026)
This paper examines spatial, demographic, and functional transformations in the Maribor city region through case studies of four cities—Šentilj, Miklavž, Maribor Studenci, and Kidričevo—located along the southern part of the Maribor–Graz corridor. Based on field surveys, interviews, municipal consultations, and direct observation conducted between 2024 and 2025, the study identifies suburbanisation, cross-border mobility, and post-industrial restructuring as the key processes shaping contemporary settlement development. Although each settlement exhibits distinct historical and economic trajectories, they share common challenges related to housing pressures, mobility patterns, demographic change, and administrative fragmentation. The findings show that the region is becoming increasingly integrated into an urban agglomeration influenced by labour migration to Austria and the central role of Maribor as the main employment centre. The paper concludes that coordinated spatial planning, sustainable mobility improvements, and strengthened cross-municipal cooperation are essential for managing future development within this evolving urban–suburban landscape.